Formulation and Characterization of Cu-Zn-V-Al Oxides Catalyst in Auto Thermal Reforming of Methanol. - Mahmud, Mohd Sabri; Yaakob, Zahira; Daud, Wan Ramli Wan; Mohamad, Abu Bakar (Penerbit Universiti Sains Malaysia, 2004)
Nowadays the world concern about the alternative solutions to the combustion engine due to the problem of the decreasing resources of crude oil and its recent environmental impact. One of the attention that are paid by most of the automotive industries is proton exchange membrane fuel cell (PEMFC). To comply with the modern automobiles a fast and highly responsive supply of hydrogen with no byproduct other than carbon dioxide must be found. The high selectivity requirement emanate from the sensitivity of the PEM containing Pt as the catalyst for proton exchange.